Pancreatic Biopsy as a Procedure for Detecting In Situ Autoimmune Phenomena in Type 1 Diabetes - Akihisa Imagawa; Toshiaki Hanafusa; Shinji Tamura; Makoto Moriwaki; Naoto Itoh; Koji Yamamoto; Hiromi Iwahashi; Kazuya Yamagata; Masako Waguri; Takao Nanmo; Sae Uno; Hiromu Nakajima; et al. (2001)
To better understand the pathogenesis of type 1 diabetes, we have developed pancreatic biopsy under laparoscope for recent-onset type 1 diabetic patients. The patients included 29 acute-onset type 1 diabetic patients, 5 latent-onset type 1 diabetic patients, and 1 type 2 diabetic patient. Their median age was 28 years, and the duration of diabetes at the time of biopsy was ∼3 months. In 31 of 35 patients, we could obtain the pancreas tissue by punching. No serious complications, such as heavy bleeding, peritonitis, or pancreatitis, have been experienced. Pneumoderma was observed in two patients, and abdominal dull pain had continued for 2 days in two patients. However, special treatment was not necessary for these complications. T-cell–predominant infiltration to islets (insulitis) and hyperexpression of major histocompatibility complex class I antigens on islet cells were the two major findings and were observed in 17 of 29 recent-onset type 1 diabetic patients. These findings could be regarded as evidence of immune attack against β-cells, and their presence was closely correlated with the presence of either anti-GAD or anti–IA-2 antibodies (P = 0.02). In conclusion, pancreatic biopsy under laparoscope is a safe procedure without serious complications, according to our findings, for detecting in situ autoimmune phenomenon in recent-onset type 1 diabetic patients.